Biochemistry and Physiology of Blood Coagulation - Mann, Kenneth G. (Thrombosis and Haemostasis, 1999)
The biochemical investigation of a biological process can be divided into three segments. The first is the development of an inventory of the components involved in the process, the second is the establishment of the connectivity between components, and the third is the establishment of the dynamics of the processes as they occur in the living organism.